An Integrative Framework for the Design and Development of Islamic Religious Education (PAI) in the Digital Era - Laila Rahmi Hasanah; Mona Alyaa Sausan; Lailatul Mukjizat; Abu Mansur; Baldi Anggara (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study aims to analyze the nature, scope, and development of Islamic Religious Education (PAI) learning design in the digital era. The study employs a qualitative library research method with a descriptive-analytical approach by examining relevant literature on instructional design, Islamic education, and digital learning. The findings reveal that PAI learning design is a systematic and integrative process that connects learning objectives, materials, strategies, media, and evaluation while emphasizing the integration of cognitive, affective, and psychomotor domains. The study also finds that the development of PAI learning is a continuous process grounded in both technological advancement and Islamic principles, particularly the concept of self-evaluation (muhasabah) as reflected in Qur’anic teachings. In addition, the scope of PAI learning design includes student analysis, objective formulation, material selection, strategy and method determination, media utilization, and comprehensive evaluation. The study further clarifies the conceptual distinctions among instructional design, models, strategies, and methods, which are often used interchangeably in educational practice. The novelty of this study lies in its integrative conceptual framework that combines instructional design theory, digital transformation, and Islamic educational values. This study contributes to the development of more adaptive, value-oriented, and meaningful PAI learning in the digital era.